2011
DOI: 10.1111/j.1365-2206.2011.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of foster children's behavioural problems on Flemish foster mothers' parenting behaviour

Abstract: Professor, ‡Researcher, Department of Clinical and Lifespan Psychology, Vrije Universiteit Brussel, †Opvang vzw afdeling Brabant, Brussels, Belgium A B S T R AC TFoster children often have behavioural problems. Behavioural problems influence the level of parenting stress and can lead to a breakdown. In this study, parenting behaviour of foster mothers is mapped, and the influence of behavioural problems and parenting stress on the parenting behaviour 2 years later is examined. Data of behavioural problems, fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 24 publications
1
52
0
Order By: Relevance
“…Additionally, adverse or inconsistent caregiving tends to cause atypical functioning of children’s biological stress systems, such as changes in the hypothalamic-adrenal-pituitary (HPA) axis, represented by abnormal cortisol segregation [12,13], and altered stress regulation activity of the autonomic nervous system (ANS) [14]. After placement in foster care, problems tend to persist or even worsen [15,16], and not only negatively affect the parenting behavior of foster carers [17] but also increase the risk of placement breakdown. Placement breakdown may start a vicious circle in which the chance of another failure increases with every breakdown [18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, adverse or inconsistent caregiving tends to cause atypical functioning of children’s biological stress systems, such as changes in the hypothalamic-adrenal-pituitary (HPA) axis, represented by abnormal cortisol segregation [12,13], and altered stress regulation activity of the autonomic nervous system (ANS) [14]. After placement in foster care, problems tend to persist or even worsen [15,16], and not only negatively affect the parenting behavior of foster carers [17] but also increase the risk of placement breakdown. Placement breakdown may start a vicious circle in which the chance of another failure increases with every breakdown [18].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the evidence of general and specific interventions for foster parents is of great importance to practice. It may help foster parents ‘do the right things’, for instance, using positive discipline practices and becoming more supportive towards their foster child (Vanderfaeillie et al . 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also found that negative parenting strategies have a greater impact on behaviour problems than does the mere absence of positive relationships (Vanderfaeillie et al . ).…”
mentioning
confidence: 97%
“…By contrast, a rigid and aggressive parenting style has been associated with poorer outcomes as regard behaviour problems (Schofield & Beek , ; Fernandez ). In a recent study, Vanderfaeillie and colleagues () showed that problem behaviour decreased when foster parents were more engaged with their foster children, teaching them rules, guiding their behaviour and encouraging them to be more independent.…”
mentioning
confidence: 99%